Association Between Melanoma Risk and Height: A Narrative Review - Gino A. Vena; Nicoletta Cassano; Stefano Caccavale; Giuseppe Argenziano (Mattioli1885, 2019)
The link between anthropometric indices, including height, and cancer risk and/or progression has attracted considerable interest in recent years. Adult height results from the complex interplay between genetic, hormonal, nutritional, and other environmental factors and has been found to contribute to the risk of several selected malignancies, although it has not been implicated as a real cause per se. A number of studies have investigated the height-melanoma relationship, showing controversial results so far. In this review, we summarize the epidemiological data regarding the association between height and melanoma risk and analyze the potential underlying mechanisms.